Distance and Direction Matters: Risk Perception Among Residents Around a Dump Yard in Kerala, India - Payyappilly AP; Babu P; Nair MR (Risk Management and Healthcare Policy)
Antony Paul Payyappilly, Priya Babu, Manju R Nair Achutha Menon Centre for Health Science Studies, Sree Chitra Tirunal Institute for Medical Sciences and Technology, Thiruvananthapuram, Kerala, IndiaCorrespondence: Manju R Nair, Achutha Menon Centre for Health Science Studies, Sree Chitra Tirunal Institute for Medical Sciences and Technology, Thiruvananthapuram, Kerala, India, Email manjun@scitmst.ac.inPurpose: Waste mismanagement is a growing concern in developing countries where unsustainable practices such as open dumping and open burning are rampant. This study examined the risk perceptions of the residents living in proximity to the Brahmapuram dump yard, situated in Ernakulam district of Kerala State, India- A site marked by persistent local protests, public outrage, and legal disputes arising from issues related to waste mismanagement. The study focused on the geospatial and sociodemographic factors that might influence these perceptions.Patients and Methods: A cross-sectional survey was conducted among 302 respondents living within 4 kilometers from the borders of the dump yard using a structured interview schedule. The responses of the participants were used to compute a risk perception score, which reflected participants’ risk perception regarding the environment and their health.Results: Among the participants in the study, those who lived within 2 kilometers (2.3 (95% CI 0.96, 3.7; p< 0.001)), those who lived to the east (2.7 (95% CI 1.1, 4.2; p< 0.001)) and those who reported perceiving strong malodor from the dump yard (2.0 (95% CI 0.54, 3.4; p=0.007)), had a higher risk perception in the multivariate linear regression model. Women had a lesser risk perception compared to men (− 2.6 (95% CI − 3.7, − 1.4; p< 0.001)).Conclusion: The findings highlight the importance of geospatial characteristics (distance and direction), malodor and gender differences in shaping the risk perceptions among the proximate residents living around a waste dump yard. Consideration of geospatial and sociodemographic determinants in risk assessment and management could potentially reduce the perceived risks and public discontent around waste management facilities.Keywords: geospatial analysis, waste management, waste dump yard, urban health, Kerala, India